Surgical Salvage of Microcatheter-induced Aneurysm Perforation During Coil Embolization - Short, John G.; Marx, William F.; Lanzino, Giuseppe; Ellegala, Dilantha B.; Kassell, Neil F. (American Journal of Neuroradiology, 2002)
Summary: We report a case of iatrogenic aneurysm rupture during coil embolization in a 55-year-old woman. Surgical intervention resulted in a good clinical outcome. To our knowledge, this technique for the salvage of catheter-induced aneurysm perforation has not been previously reported.